2014
DOI: 10.1111/jmwh.12071
|View full text |Cite
|
Sign up to set email alerts
|

A Usability Study of a Mobile Health Application for Rural Ghanaian Midwives

Abstract: Midwives in rural Ghana work at the frontline of the healthcare system, where they have access to essential data about the patient population. However, current methods of data capture, primarily pen and paper, make the data neither accessible nor usable for monitoring patient care or program evaluation. Electronic health (eHealth) systems present a potential mechanism for enhancing the roles of midwives by providing tools for collecting, exchanging, and viewing patient data as well as offering midwives the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 24 publications
4
65
0
1
Order By: Relevance
“…Usability also interplays significantly with technological factors, such as mobile broadband signal – such factors enhance or detract from a system’s overall usability (even the most user-friendly app will not work if there is no signal). Features of usability can be as simple as screens that require less scrolling [30], or difficulty with usernames and passwords [21]. Such issues may seem small and easy to overcome during piloting, but when a project is brought to scale these seeming inconveniences can limit the workflow of thousands of health care workers and negatively affect clinical care.…”
Section: User Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usability also interplays significantly with technological factors, such as mobile broadband signal – such factors enhance or detract from a system’s overall usability (even the most user-friendly app will not work if there is no signal). Features of usability can be as simple as screens that require less scrolling [30], or difficulty with usernames and passwords [21]. Such issues may seem small and easy to overcome during piloting, but when a project is brought to scale these seeming inconveniences can limit the workflow of thousands of health care workers and negatively affect clinical care.…”
Section: User Considerationsmentioning
confidence: 99%
“…For instance, midwives in Ghana were dismissive about any device with free text fields that were meant to include subjective information, as they only cared about a small amount of data, which they needed to include in their daily reports [30]. Many studies have shown that sending medical information through short messages becomes difficult with a 160-character limit, or when people speaking multiple languages are involved [14].…”
Section: User Considerationsmentioning
confidence: 99%
“…[25] Similarly, a usability study of a mobile health application for Ghanaian midwives found difficulty operating a small onscreen keyboard, selecting buttons on a smartphone screen, a safety risk in lack of application password, and difficulty adding new patients to the system. [37] Another study of an mHealth application for tuberculosis treatment in rural South Africa found poor uptake among healthcare workers despite high reported acceptability, largely due to difficulty uploading patient information. [38]…”
Section: Discussionmentioning
confidence: 99%
“…In general, studies show that aligning software design with the requirements of these health workers is extremely challenging due to unpredictable work environments, privacy and security issues involved in storing and sharing data, and technical know-how of the target users [28]. The limitation of current research is that most of it has been done in the developing world.…”
Section: Introductionmentioning
confidence: 94%